EFFECTIVENESS OF AN INTERVENTION IN IMPROVING HEALTHCARE WORKERS’ KNOWLEDGE OF ANAPHYLAXIS DIAGNOSIS AND MANAGEMENT IN THAI BINH, VIETNAM, 2025 (Vietnam Journal of Community Medicine, 2026)
Aims: To evaluate the effectiveness of a training intervention in improving healthcare workers’ knowledge of anaphylaxis diagnosis and management in Thai Binh province.Methods: A pre–post intervention study was conducted among 150 healthcare workers (50 physicians and 100 other healthcare workers) from four hospitals and four commune health stations in Thai Binh, from May 1 to December 31, 2025. The intervention was an 8-hour training program including 4 hours of lectures and 4 hours of hands-on practice using simulation models and case discussions. Knowledge was assessed using a structured questionnaire with 22 items on diagnosis (maximum 30 points) and 20 items on management (maximum 20 points). Adequate knowledge was defined as ≥80% correct answers. Participants were surveyed immediately before the training and one month after completion.Results: The median age was 34 years (Q1–Q3: 28–39), 74,0% were female, and the median length of service was 10 years (Q1–Q3: 4-15). The total diagnostic knowledge score increased from 24.7 (SD 2.79) to 25.9 (SD 2.23), with a mean difference of +1.12 points (SD 3.41; 95% CI: 0.57 to 1.67). The total management knowledge score increased from 15.5 (SD 2.02) to 17.2 (SD 1.60), with a mean difference of +1.71 points (SD 2.49; 95% CI: 1.31 to 2.11). The proportion of participants achieving adequate diagnostic knowledge increased from 69.3% to 88.0% (+18.7 percentage points), and the proportion achieving adequate management knowledge increased from 60.0% to 92.7% (+32.7 percentage points).Conclusion: The 8-hour combined lecture-and-practice training program significantly improved healthcare workers’ knowledge of anaphylaxis diagnosis and management at one-month follow-up and substantially increased the proportion meeting the predefined adequacy threshold (≥80%).
Keywords: knowledge, healthcare workers, anaphylaxis, diagnosis, management, Thai Binh.